A rare occurrence of mucocele in the floor of the mouth of an infant - Asmita Sodhi; Deepinder P S. Sodhi; Gursimrat K Brar; Surinder P S. Sodhi (Journal of Pharmacy and Bioallied Sciences, 2024)
A mucocele is a prevalent benign oral lesion distinguished by the extravasation or retention of mucous within submucosal tissue originating from minor salivary glands. Mucoceles predominantly manifest on the lower lip, followed by occurrences on the floor of the mouth and the buccal mucosa. Trauma and lip biting habits are one of the main causes of lesions. Mucoceles are rarely observed in infants. This paper highlights an atypical case of mucocele located within the floor of the mouth in the first year of life (9 months old) in a child who was treated successfully with complete surgical excision, and the patient is on regular postoperative follow-up.